Cause-Effect: The Relationship between Role and Experience with Psychological and Physical Responses in the Competition Context in Soccer Referees - Castillo-Rodríguez, Alfonso; Rodríguez-Caparrós, Jesús Lorenzo; Figueiredo, Antonio; González-Fernández, Francisco Tomás; Onetti, Wanesa (Journal of Human Kinetics, 2024)
This study analyzed the effects of psychological responses (impulsivity, self-esteem, self-confidence, and anxiety) in baseline and pre-competitive contexts of national soccer referees (SRs), their control of the game (yellow and red cards), and physical performance (PP) according to the role (assistant or main referee), and experience in the category. Twenty-seven national SRs from Spain participated in this study. Baseline and pre-competitive psychological data were collected through the Competitive State Anxiety Inventory-2 (CSAI-2 test), Urgency, Premeditation (lack of), Perseverance (lack of), Sensation Seeking, Positive Urgency, Impulsive Behavior Scale (UPPS-P test), and Rosenberg tests. Furthermore, WIMU PRO™ inertial devices were used to monitor PP. The results indicated that a lack of perseverance and self-esteem were higher in the main SRs and somatic anxiety in assistant SRs. Experience of SRs was related to anxiety, self-confidence, self-esteem, impulsivity dimensions, and PP metrics (p < 0.05). Finally, red cards were related to positive and negative urgency (r = 0.38 and r = 0.35, p < 0.05, respectively). In conclusion, the main SRs and SRs with more experience had better psychological characteristics and PP in a competitive context. However, yellow and red cards were not associated with these factors, although red cards were related with urgency. Based on these data, specific training programs could be incorporated to enhance emotional control in SRs with less experience to achieve greater performance and professional development.
Keywords: self-esteem; self-confidence; impulsivity; anxiety; performance; GPS